Obligations of a Husband with Convict Status from the Perspective of Islamic Law and Positive Law - Isman, Isman; Lukman S. Thahir; Usdar Suwandi; Ikram, Ikram (State Islamic University Datokarama Palu, 2024)
This study aims to investigate the obligations of a husband with convict status from the perspective of Islamic law and positive law. This study used a case study qualitative method. Data were gathered through direct observation, in-depth interviews, and written document analysis. Data were analyzed using the thematic approach outlined by Corbin and Strauss. The results of this study show that The implementation of the obligation of physical support by a husband who has the status of a prisoner in the penitentiary is divided into three groups, namely first, it is carried out on the grounds that there is a form of effort made by the prisoner's husband, such as a business that is still running and producing results that the wife can use to meet her daily needs. The obligation of support for a husband who is serving a sentence does not conflict with Islamic law and Positive law even though, on the one hand, he still has the status of a head of the family who has obligations that must be fulfilled. Islam views this as three legal provisions, namely the first is that the obligation of support remains, the second is that the obligation of support becomes a debt, and the third is that the obligation of support is terminated.